Prophetic Leadership in the Role: Building Madrasah Culture and Harmonious Interpersonal Relationships with the Community - Sukandi, Ria; Muhammad, Muhammad; Agus, Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Today, leadership has become a growing discourse among many groups, including practitioners, observers, and even in public spaces, emphasizing the ideal form of leadership that is dynamic and relevant to everyday life. Madrasas, as Islamic educational institutions, play a strategic role in shaping a generation that is knowledgeable, moral, and competitive. However, the challenges of the era of globalization and modernization demand a leadership model that is not merely administrative, but also transformative and based on spiritual values. This article aims to analyze the concept of prophetic leadership in building madrasa culture, interpersonal and its relationship with society, and transcendence in educational leadership. The research method uses a literature study approach. The results of the study indicate that prophetic leadership contributes significantly to strengthening the madrasa vision, building an academic culture of integrity, and improving the quality of human resources. Thus, prophetic leadership in building madrasa culture becomes a relevant paradigm for strengthening the role of madrasas in facing the challenges of the times.